Depression and anxiety in children and adolescents with epilepsy: Prevalence, risk factors, and treatment - ARMAN, AYŞE (ACADEMIC PRESS INC ELSEVIER SCIENCE, 2009)
Among the psychiatric comorbid conditions in children and adolescents with epilepsy, depression and anxiety disorders require further attention because they carry the risk of reduced quality of life and life-threatening complications (e.g., Suicide). Research in recent years has shed light on both the prevalence of emotional problems in youth with epilepsy and the safety and efficacy of treatment options. A number of challenges exist in treating patients with epilepsy. This is particularly true when seizures are difficult to control and medication regimens are more complex. Some pharmaceutical options may provide assistance with both seizures and emotional distress, but care is needed when considering such treatment approaches. In addition. integration of mental health professionals into the care of patients is necessary when cases are complicated and risk factors are high. Thorough methods to accurately diagnose emotional conditions and regular monitoring of symptoms can help prevent serious problems that can negatively affect the success of children and adolescents in everyday life. Collaboration between disciplines offers the best hope for early identification and treatment of these conditions. (C) 2008 Elsevier Inc. All rights reserved.
Keywords: Epilepsy; Children; Adolescent; Depression; Anxiety; TEMPORAL-LOBE EPILEPSY; QUALITY-OF-LIFE; SEROTONIN REUPTAKE INHIBITORS; RESISTANT UNIPOLAR DEPRESSION; COMPLEX PARTIAL SEIZURES; BEHAVIOR PROBLEMS; ANTIEPILEPTIC DRUGS; PEDIATRIC EPILEPSY; MAJOR DEPRESSION; OPEN-LABEL